Post-editing wildlife documentary films: a new possible scenario? - Carla Ortiz-Boix; Anna Matamala (JoSTrans: The Journal of Specialised Translation)
Several studies have proven that, when machine translation followed by post-editing is used to translate general and specialised texts, there is an increase in the productivity, as the post-editing effort is lower than translating ex novo. Although the use of machine translation and post-editing has been investigated in Audiovisual Translation, this has never been researched in non-fictional audiovisual genres in which voice-over and off-screen dubbing are applied. Using an English wildlife documentary film as the source text, and Spanish as the target language, this study intends to research whether post-editing involves more or less effort than translating a documentary. Conclusions on the experiment described in this article, in which 12 Audiovisual Translation MA students took part, seem to indicate that post-editing involves less effort than translating.